Thermal performance of a thermoacoustic stack - Habeed Mohd. Abd Settar, Nurudin (2008)
The heat transfer process crucial to the thermoacoustic effects occurs in and near the stack region and current technology of the stack material and geometry has room for improvement. The latest recommended stack material is Mylar and it has been theoretically proven that pin-array stack performs better than other geometry. Stack gap recommended varies between researchers using different material and geometry. This study looked into the stack performance in terms of the temperature difference achieved between the stack ends for various locally available materials at different thickness and geometry. Experiments were conducted using PVC resonator tube with paper and film material as stack, at 0.1 and 0.2mm thickness. Parallel plate, spiral roll and the honeycomb geometry were tested. Results showed that the parallel plate stack made from the film gave higher temperature difference compared to that from paper operating with a stack gap of 0.45mm. A maximum of 3.5Â°C below the ambient temperature was achieved at the â€œcoldâ€? end for the system operating at 1atm and 22~24Â°C.